ACCIONES DE MAESTROS DE CIENCIAS: CREENCIAS, ROLES, METAS Y CONTEXTOS EN LA ENSEÑANZA Y EL APRENDIZAJE - Reyes Herrera, Lilia Reyes Herrera; Enrique Salcedo, Luis (Tecné, Episteme y Didaxis: TED, 1998)
Although scence curricula vary widely among countries, states, school districts, individual schools and individual classrooms, the understanding and enhancement of science teaching and learning is so limited in most of them that it is a global concern. Teacher’s conceptions play an important role in the implementation of a science curriculum, consequently; the study and development of teacher conceptions of the nature of science education has become one of the most important goals of the science education community. Although in the last twa decades this has been a prolific area of research, it is yet to be researched more deeply. The overallpurpose of this research is to explore the nature of the referents used by science teachers when engaged in science instruction and to elucidate patterns of beliets, goals, roles and context which guide teachers actions and interactions. The kind of research we are doing argue tora change in teachers’ epistemology empowering them to take informed decisians to break away fram dominant practices which have been present ín the community without deep questioning.